Fabrication and interfacial modification of wood/recycled plastic composite materials - Cui, Y.; Lee, S.; Noruziaan, B.; Cheung, M.; Tao, J.
In this study, wood/recycled plastic composite (WRPC)material was fabricated with post-consumer high density polyethylene (HDPE)and wood fiber using a single-screw extruder. To improve the interfacial adhesion between the wood fiber and the HDPE, a coupling agent, maleic anhydride modified polypropylene (MAPP), together with three surface treatments (an alkaline method, a silane method and an alkaline followed by silane method)were used to treat the wood fibers. The surface chemistry of the treated fibers was evaluated using FTIR techniques. The effects of wood fiber length, weight fraction and surface treatment on the mechanical properties of WRPC materials were investigated. Fracture surfaces of tested WRPC specimens were examined and the fracture mechanism of WRPC materials is also discussed in this paper. Test results indicate that WRPC material with wood fiber treated by the alkaline followed by silane treatment method together with the MAPP coupling agent possesses good mechanical properties. The content of wood fiber affects the flexural strength, flexural modulus, and impact strength of these WRPC materials.
Keywords: WOOD; RECYCLING; FIBER/MATRIX BOND; SURFACE TREATMENTS